Plan semillas de maíz duro de alto rendimiento (MAGAP), costos de producción y rentabilidad en el cantón Mocache Provincia de Los Ríos. - Zambrano Alvarado, Gregorio Alejandro (2016)
This study is a descrptive screening focused on the analysis of the direct and indirect production costs associated with the profitability of maize (Zea Mays L.) Whose development involves the use of the inductive and analytical methods to primary and secondary sources that allow the collection of data required for research. In each Plan Segments high, medium and low seed kits in the Mocache canton in Los Ríos province, small and medium-sized farmers benefit from a State subsidy of $214,00 and in addition have free technical advice from an engineer who visits every farm. In relation to indirect costs that the corn’s production implies is performs an analysis of them activities developed by them producers for to assess their profitability and for mature results reliable is makes an investigation of data through surveys made to 325 producers taken to the random of a lists from 1241 farmers and them results obtained were tabulated and collated by relationship percentage. Results analysis determined the importance of this activity in the economy of 71% of family furthermore the benefit/cost relationship shows that profitability will vary depending on the kit that is selected throwing even leaks representing falls in the annual production of this grass that currently is the grain of greatest consumption worldwide.